Digital Transformation of Global English Literacy in Secondary Education - Anggreni, Afrillia; Ahmar, Dewi Satria; Patmasari, Andi; Azzajjad, Muhammad Fath (Journal of Applied Science, Engineering, Technology, and Education, 2026)
Digital transformation is increasingly influencing English literacy education in secondary schools; nonetheless, differences in technology utilisation and its effects persist among institutions. This study investigates the correlation between students' preferences and the frequency of digital learning methodologies and technology integration in the advancement of English literacy. A quantitative descriptive–correlational cross-sectional design was utilised, employing a 20-item Likert questionnaire. The population consisted of senior high school students in Palu City, Indonesia, with a sample of 469 students from five schools chosen via purposive and convenience sampling methods. The results show a very significant link between Group 1's choice for digital methods and Group 2's impact on technology integration and literacy (r = 0.872; r² ? 0.761). The total visual correlation is r = 0.918. The average perception score was M = 76.89 (SD = 9.23). These results show that basic digital skills have a big impact on literacy outcomes. This means that teachers need more training in digital skills and schools need better infrastructure to facilitate long-term changes in education.